The Effectiveness of Educator Training in Implementing English as a Medium of Instruction in Algerian Universities - Nadia MENEZLA & Boualem BENGHALEM (Akofena, 2024)
Abstract: This study evaluates the effectiveness of training programs designed for Algerian university instructors who use English as a medium of instruction (EMI). It explores the challenges faced by these educators and how teacher preparation programs address these issues. Specifically, the research assesses instructors' confidence and readiness in utilizing EMI within Algerian institutions, as well as their attitudes toward the transition from French to English as the primary language of instruction. A 31-item questionnaire was administered to a sample of Algerian university educators from various institutions. The findings reveal a preference for English over French as the medium of instruction, largely due to the advantages of globalization and the accessibility of resources in English. The study emphasizes the importance of effective teacher training programs in enhancing instructors' confidence, pedagogical skills, and English language proficiency, ultimately leading to improved teaching quality and student learning outcomes.